The Relationship between Self Boundaries and People Pleaser Behavior in Islamic Guidance and Counseling Students at UIN Raden Mas Said Surakarta / Hubungan Self Boundaries Terhadap Perilaku People Pleaser Pada Mahasiswa Bimbingan dan Konseling Islam di UIN Raden Mas Said Surakarta - Zalika, Farras Raisa; Nisa, Athia Tamyizatun (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2024)
Self boundaries are important for students to apply in everyday life in order to have clear boundaries. The impact of individuals who do not have clear and firm self-boundaries causes people pleaser behavior. Self boundaries play a role in helping efforts to deal with mental and emotional well-being. This study aims to determine the relationship between self boundaries and people pleaser behavior in Islamic Guidance and Counseling students at UIN Raden Mas Said Surakarta. The research method used in this study is quantitative with a correlational approach. The sample technique uses systematic random sampling, the sample of this study is Islamic Guidance and Counseling students at UIN Raden Mas Said Surakarta which is obtained by 112 students. The results of the data analysis of this study using Pearson product moment correlation hypothesis test produced a value with a significance value of 0.000. These results indicate that there is a significant relationship between self boundaries and people pleaser behavior in Islamic Guidance and Counseling students at UIN Raden Mas Said Surakarta with a significant and positive direction.